Effects of essential fatty acids and branched-chain amino acids in lactation diets on sow and litter performance - Holen, Julia Perrine (Kansas State University, 2022)
This dissertation is comprised of 5 chapters consisting of a review of literature on branched-chain amino acids (BCAA) in lactation diets, a meta-regression analysis to evaluate the effects of BCAA on sow and litter growth performance, evaluation of the effects of essential fatty acids (EFA) in lactating sow diets on sow reproductive performance, colostrum and milk composition, and piglet survivability, supplementation of fat sources and pre-farrow EFA intake on lactating sow performance and EFA status, and the effects of increasing soybean meal in corn-based diets on growth performance of late finishing pigs. Chapter 1 presents a review of the literature on the effects of BCAA on sow mammary gland metabolism, colostrum and milk composition, and sow and litter performance. Chapter 2 describes a meta-regression analysis conducted to evaluate the effects of BCAA and their interactions in lactating sow diets to predict litter growth performance, sow bodyweight change, and sow feed intake. The results suggest that Ile, Leu, and Val play an important role in litter growth, sow bodyweight change, and sow feed intake during lactation; however, the influence of BCAA on these criteria is much smaller than that of other dietary components such as net energy, SID Lys, sow average daily feed intake, and crude protein. In Chapter 3, mixed-parity sows and their litters were used to evaluate the effects of EFA intake on sow reproductive performance, piglet growth and survivability, and colostrum and milk composition. Overall, sows consuming high EFA produced litters with heavier piglet weaning weights and greater litter average daily gain (ADG) when compared to litters from sows fed diets with low EFA. However, there was no impact of sow EFA intake on piglet survivability or subsequent sow reproductive performance. Chapter 4 describes a study evaluating the effects of supplemental fat sources and pre-farrow EFA intake on lactating sow and litter performance and EFA composition of colostrum, milk, and adipose tissue. The results suggest that providing dietary fat sources with high concentrations of EFA can increase colostrum linoleic acid and α-linolenic acid concentrations that are maintained throughout lactation. However, the changes in colostrum and milk composition did not alter litter growth performance in this experiment. Lastly, Chapter 5 presents three experiments that were conducted to determine the effects of increasing soybean meal levels in replacement of feed-grade amino acids in corn-based diets on growth performance of late finishing pigs raised in commercial facilities. The combined results of the three experiments suggest that inclusion at least 4 to 8% dietary SBM at the expense of feed-grade amino acids in corn-based diets with or without grain co-products can improve growth performance of late-finishing pigs.
Keywords: Sow; Lactation; Litter performance; Essential fatty acids; Amino acids; Swine